Editorial - Lund, Jacob (The Nordic Journal of Aesthetics, 2012)
With no over-arching theme, this issue of The Nordic Journal of Aesthetics presents a diversity of articles that under different perspectives deal with a variety of different topics and medialities, ranging from a critical theoretical exploration of the faculty of judgement, over an analytic evaluation of architectural value, to an enactive approach to aesthetic preference and the bodily conditions of meaning constitution.